1998
DOI: 10.1093/nar/26.17.4056
|View full text |Cite
|
Sign up to set email alerts
|

Distinct frequency-distributions of homopolymeric DNA tracts in different genomes

Abstract: The unusual base composition of the genome of the human malaria parasite Plasmodium falciparum prompted us to systematically investigate the occurrence of homopolymeric DNA tracts in the P. falciparum genome and, for comparison, in the genomes of Homo sapiens , Saccharomyces cerevisiae , Caenorhabditis elegans , Arabidopsis thaliana , Escherichia coli and Mycobacterium tuberculosis. Comparison of theobserved frequencies with the frequencies as expected for random DNA revealed that homopolymeric (dA:dT) tracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
2
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 46 publications
5
93
2
3
Order By: Relevance
“…In budding yeast, homopolymeric dA:dT tracts (referred to here as polyA tracts) of ≥10 bp occur in the genome well above what is expected based on random chance ( Fig. 5C; Dechering et al 1998). Analyzing the association that polyA tracts of incremental length have with hybrid formation, we noted a sharp transition to near-perfect overlap for polyAs of ≥21 bp (Fig.…”
Section: Sequence Features Of Hybrid-prone Regionsmentioning
confidence: 71%
“…In budding yeast, homopolymeric dA:dT tracts (referred to here as polyA tracts) of ≥10 bp occur in the genome well above what is expected based on random chance ( Fig. 5C; Dechering et al 1998). Analyzing the association that polyA tracts of incremental length have with hybrid formation, we noted a sharp transition to near-perfect overlap for polyAs of ≥21 bp (Fig.…”
Section: Sequence Features Of Hybrid-prone Regionsmentioning
confidence: 71%
“…However, it has been suggested that cpSSRs of length 8 nt or more (regardless of repeat motif) are prone to slip-strand mispairing (SSM, thought to be the primary mutational mechanism to affect SSRs), whereas those of lesser length are not (Rose and Falush, 1998). Elsewhere, the critical threshold is estimated at 7-10 bp (Dechering et al, 1998).…”
Section: Frequency and Distribution Of Cpssrs In The Poaceae Species mentioning
confidence: 99%
“…These types of boundaries can be formed by nucleosome attracting signals, or nucleosome repelling signals such as poly(dA:dT) tracts (Bernstein et al 2004;Yuan et al 2005;Lee et al 2007;Field et al 2008;Kaplan et al 2009). Imperfect boundaries such as those that result over poly(dA:dT) tracts are common in eukaryotic genomes (Dechering et al 1998), indicating a possible functionality for these sequence-encoded signals. Indeed, when located within promoter regions, these sequences are hypothesized to have important effects on transcription (Struhl 1985;Iyer and Struhl 1995).…”
Section: Addition Of Boundary Elements For Nucleosome Formation Shiftmentioning
confidence: 99%